PERAN AKTIF ORANGTUA DAN GURU SEKOLAH INKLUSI DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN INTERAKSI SOSIAL ANAK PENDERITA AUTISME - Dilla Dilla Astarini (Psikodidaktika, 2020)
Abstract This research was carried out at the Al-Aufa Integrated Islamic Primary School Inclusion Program in Bengkulu City. The purpose of this study is to describe the characteristics of children with autism and how the active role of parents and teachers in improving communication skills and social interactions of children with autism. This study uses a qualitative approach to the type of case study research. In this study the authors collected data by going directly to the field and conducting interviews, direct observation, and conducting documentation studies to the research location. The subjects in this study amounted to one child with autism. The data obtained were analyzed with descriptive qualitative data analysis techniques and using triangulation techniques to check the validity of the data. The results of this study indicate that there is a significant relationship between the active role of parents and inclusive school teachers in improving communication skills and social interaction of children. The most important thing given to children is parents' acceptance of children and social support provided by parents and teachers in the environment around children. The conclusion of this study is that children with autism require very complex handling and require the participation and active role of parents and teachers in many matters related to the development of communication and social interaction of children. Keywords: Communication skills, Social interactions, Autism